The Greek Scribe Neophytos and the Oldest Attested Name for the Monastery of Panagia Archangeliotissa near Xanthi - GETOV, Dorotei (Byzantina Symmeikta, 2015)
Eight liturgical manuscripts, kept now in the library of The Ecclesiastical Historical and Archival Institute (EHAI) of the Patriarchate of Bulgaria in Sofia1, were copied by the monk Neophytos who is the subject of the present communication. In addition to his scribal colophons, Neophytos wrote two dedication notes, transcribed below, which reveal how the monastery of Panagia Archangeliotissa was called in the 3rd quarter of the 16th century.